The shuttle nanoelectromechanical nonvolatile memory - Pott, Vincent (2013)
Nonvolatile memory (NVM) devices based on storage layers, p-n junctions and transistors, such as FLASH, suffer from poor retention at high temperature, high voltage writing, and wear out while cycling. This paper presents the structure, operation, and modeling of a nanoelectromechanical NVM based on the switching of a free electrode between two stable states. This electrode, called the shuttle, has no mechanical anchors and commutes between two positions. It is guided inside an insulator pod. Adhesion forces between the shuttle and fixed electrodes serve to hold the shuttle in stable positions. Smooth metal layers give strong Van der Waals stiction between two surfaces in contact. Memory detection is obtained by probing the conductance between two fixed contacts; the shuttle serves as a switchable open/short electrode. Electromechanical contacts have an ideally large resistance ratio between on and off levels. At microscale, gravity is found to be negligible compared with adhesion forces, which motivates the anchorless design for high-temperature data storage. The model proposed is based on charge induction over the surface of metal electrodes and is validated by finite-element method. Kinematic equations and energy transfers of the shuttle device are explored. Due to its unique anchorless design, the scalability of the anchorless shuttle memory is found to be excellent.